Tooth mortality in a selected population in Sanaa - Al-Bayaty, F.H.; Wahid, A.U.; Bulgiba, A. (2006)
Tooth loss is the dental equivalent of mortality. It is the end product of oral disease, since tooth loss is the ultimate result of untreated dental caries and periodontal disease, tooth mortality figures such as the mean number of missing teeth are recognized as being a crude but useful measure of the oral health status of community. In Yemen- Sana'a although a limited number of epidemiological studies have revealed oral disease patterns typical of many Third World countries, very little information is available on patterns of tooth mortality despite the simplicity of the survey methods required to assess tooth loss. The present study was designed to examine tooth mortality in a selected Yemenites sample, and to examine the patterns of tooth loss over a wider age range. A total of 2506 persons ranging from 15 to 64 years were examined, the status of every permanent tooth, third molar teeth were not included in the study on account of their frequent impaction or agenesis. Missing teeth included both extracted teeth and missing teeth. The number of teeth loss per person was calculated and this mean was used for all tests. The t test and analysis of variance (ANOVA) test were performed to compare the means between groups. Mean tooth loss increases with the age group and is the highest in old age group. The severity of tooth loss was higher in females than in males in all age groups and the differences is highly significant, females also represent higher mean tooth loss in upper and lower jaws compared to males and the difference is significant. The mean number of lost teeth at different age group in this study was approximately equal to that in Australia and more than in China and less than that for se!,eral western contouries. The predominant loss teeth are the first and second molars in the total sample, while incisors, laterals and canines represent a high significant mean loss in male than female. This study has shown that the severity of tooth loss among the total mean teeth loss by age and gender was higher in females than in males, mean tooth loss increases with the age group and is the highest in older age group.